2020
DOI: 10.3389/fphar.2020.00583
|View full text |Cite
|
Sign up to set email alerts
|

Supplement With Calcium or Alendronate Suppresses Osteopenia Due to Long Term Rabeprazole Treatment in Female Mice: Influence on Bone TRAP and Osteopontin Levels

Abstract: trabeculae and increased number of osteoclasts. Calcium or alendronate with rabeprazole showed thick bone trabeculae without full recovery from rabeprazole induced damage. Adding calcium supplementation to rabeprazole did not affect the histological abnormalities related to osteoclasts meanwhile alendronate produced inactivation of osteoclasts. Both calcium and alendronate decreased the rabeprazole-induced increment in the femur osteopontin level. Conclusion: Calcium or alendronate can be recommended for femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…OPN plays an important role in tissue remodeling, immunomodulation, and biomineralization by binding to diverse receptors, such as integrins and CD44 (165)(166)(167). In bone tissue, OPN can anchor osteoclasts to the bone mineral matrix to promote bone resorption (167)(168)(169); therefore, patients with high serum OPN concentrations have low bone mineral densities, whereas patients with low serum OPN concentrations have high bone mineral densities (170). In the brain, OPN forms different fragments after protease cleavage.…”
Section: Opnmentioning
confidence: 99%
“…OPN plays an important role in tissue remodeling, immunomodulation, and biomineralization by binding to diverse receptors, such as integrins and CD44 (165)(166)(167). In bone tissue, OPN can anchor osteoclasts to the bone mineral matrix to promote bone resorption (167)(168)(169); therefore, patients with high serum OPN concentrations have low bone mineral densities, whereas patients with low serum OPN concentrations have high bone mineral densities (170). In the brain, OPN forms different fragments after protease cleavage.…”
Section: Opnmentioning
confidence: 99%
“…Calcium is a vital nutrient for human health, accounting for about 1.5–2% of human body weight [ 1 ]. Calcium deficiency may provoke a series of diseases, such as osteopenia, osteoporosis, high blood pressure, and kidney stones [ 2 ]. Currently, there are a variety of commercial calcium supplements, including inorganic calcium, organic calcium [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes of glucose metabolism, including glucose transporter 1 (GLUT1), are regulated by HIF-1, and the expression of these genes regulated by HIF1 alters intracellular biological functions such as glucose uptake and energy production [ 7 , 8 ], which is associated with cancer cell proliferation and poor prognosis in tumours [ 9 , 10 ]. Studies have shown that ginsenoside can inhibit the growth of liver or lung cancers by inhibiting hypoxia-inducible factor-1α (HIF-1α)-mediated glucose metabolism [ 11 , 12 ]. With the deepening of research, it has been found that secondary ginsenosides and aglycones produced by the degradation of ginsenosides have stronger pharmacological effects [ 13 ].…”
Section: Introductionmentioning
confidence: 99%